Sometimes the government must solve the case: the example of a Minangkabau Land conflict - Alexander Stark (2014)
The Minangkabau society is due to its matrilineal social structure quite ‘unique’. Many anthropologists give the impression that the so-called ‘traditional’ society is able to solve conflicts and disputes. In this paper a conflict will be illustrated that could not be solved by the ‘traditional’ levels of jurisdiction. The district court had to intervene and find a solution. This case has some impacts: it shows that parts of the ‘traditional’ society are in a process of disintegration. Furthermore it shows that there is a lack of the authority of the adat dignitaries and that the people even try to be an active part of that process by putting the clan system aside and referring to a system from outside. The objective of this case study is to illustrate a conflict which concerns people who are not original inhabitants of a Minangkabau village and to show the difficulty of finding a solution.